2013
DOI: 10.4161/cc.24759
|View full text |Cite
|
Sign up to set email alerts
|

TrkB is responsible for EMT transition in malignant pleural effusions derived cultures from adenocarcinoma of the lung

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide. Recent evidence indicates that tumors contain a subpopulation of cancer stem cells (CSCs) that are responsible for tumor maintenance and spread. CSCs have recently been linked to the occurrence of epithelial-to-mesenchymal transition (EMT). Neurotrophins (NTs) are growth factors that regulate the biology of embryonic stem cells and cancer cells, but still little is known about the role NTs in the progression of lung cancer. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
(36 reference statements)
2
38
0
Order By: Relevance
“…We found here, from clinical specimens and in vitro experiments, that cancer cells in malignant PE/ascites underwent EMT and displayed a cancer stem cells phenotype, which could account for the poor prognosis. Here, besides confirming the phenomena described previously (9,19,20), we also found that malignant exudates had universal induction activity regardless of tumor type and origin. More importantly, we noted that non-CSCs could undergo EMT process and be directly converted into the CSC state when exposed to malignant PE/ascites; therefore, blocking the process in combination with conventional chemotherapies is critical to better control malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found here, from clinical specimens and in vitro experiments, that cancer cells in malignant PE/ascites underwent EMT and displayed a cancer stem cells phenotype, which could account for the poor prognosis. Here, besides confirming the phenomena described previously (9,19,20), we also found that malignant exudates had universal induction activity regardless of tumor type and origin. More importantly, we noted that non-CSCs could undergo EMT process and be directly converted into the CSC state when exposed to malignant PE/ascites; therefore, blocking the process in combination with conventional chemotherapies is critical to better control malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, VEGF was reported to induce EMT in human pancreatic cancer cells (35). Previous investigations reported that cancer cell EMT and gain of CSC properties in malignant PE/ascites depended on TrkB and TGF-␤ signaling, respectively (9,45). TrkB is a well established regulator that promotes VEGF expression (46).…”
Section: Malignant Exudates Induce Emt and Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that EMT plays a crucial role in the acquisition of invasive and metastatic potential in a number of cancers, such as head and neck squamous cell carcinoma (21), breast cancer (24), pancreatic cancer (25) and lung cancer (26). Recent studies found that the BDNF/TrkB axis is involved in the EMT process in various cancers including SACC (8,21,27). Although the correlation between EMT and PNI has been rarely reported, it is plausible to infer that EMT plays an important role in the PNI process since it can confer tumor cells with increased migration and invasion abilities (8,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…What is of considerable interest is that the BDNF/TrkB pathway has been shown to mediate the resistance to anoikis of multiple cancers (9,18,(25)(26)(27)(28)(29). it was shown that in multiple cancers, metastatic tumor cells have up-regulated TrkB and BDNF compared to tumor cells that did not metastasize (18,26,29). Furthermore, tumor cells were resistant to anchorage-independent cell death, or anoikis, because TrkB activation resulted in constitutive pi3K activity and survival for the duration of the migration to neighboring tissues (18), supporting the pro-survival role of BDNF as tumor cells migrate.…”
Section: Role In Epithelial To Mesenchymal Transition and Anoikismentioning
confidence: 99%